Bioinformatics approach to understand the mode of microbial pathogenesis of Chlamydia trachomatis and their implications in gynecologic malignancy. (August 2020) - Lin, Yanyan; Ali Abuderman, Abdul Wahab; Aldakheel, Fahad M.; Ahmad, Mohammad
Highlights: This study reports a wide range of C. trachomatis proteins that target the cellular as well as sub-cellular components of the host in gynecologic malignancy. A total of 411 proteins was identified with 79.54% maximum expected accuracy and 51.02% least expected accuracy. The highest molecular weight proteins (>80 kDa) were observed to be the targeted proteins to nucleus of host cell. There was no constant patterns observed in the values of isoelectric point (pI) in case of mitochondrial targeting. The in-silico study provided much detailed insights for further research in gynecological cancer. Abstract: Chlamydia trachomatis has a say on the target gene i.e., modulating the expression of target gene in the host so that it is given protection from the immune cells and so its survival and replication are not arrested by the host. The current study reports a wide range of C. trachomatis proteins that target the cellular as well as sub-cellular components of the host in gynecologic malignancy. Various bioinformatics tools was used to conduct an in-depth analysis on nuclear and eukaryotic sub cellular localization signal to find the sequences of the predicted proteins of C. trachomatis strain G. A total of 411 proteins was identified with 79.54% maximum expected accuracy and 51.02% least expected accuracy. There were uneven prediction of proteins along with redundancies between BaCeILo and HSLpred in the determination of sub-cellular localization of the CT proteins. The highest molecular weight proteins (>80 kDa) were observed to be the targeted proteins to nucleus of host cell. There was no constant patterns observed in the values of isoelectric point (pI) in case of mitochondrial targeting. The expression of eight proteins were significant with different fold changes. The in-silico study provided much detailed insights for further research in gynecological cancer. However, further experiments should be conducted to validate the specificity and confirmatory roles played by these predicted proteins in carcinogenesis.